Digital health and quality of care in Primary Health Care: an evaluation model - Silva, Ísis de Siqueira; Silva, Cícera Renata Diniz Vieira; Martiniano, Claudia Santos; Araújo, Aguinaldo José de; Figueirêdo, Renan Cabral de; Lapão, Luís Velez; Moioli, Renan Cipriano; Brito, Ewerton William Gomes; Uchôa, Severina Alice da Costa (Frontiers in Public Health, 2024)
The implementation of technologies in Primary Health Care with monitoring and evaluation of the quality of health care is fundamental to direct the access and quality of health care in the context of the Sustainable Development Goals. Our objective was to develop a model for evaluating digital health interventions in primary care, considering its impact on first contact, longitudinality, integrality and coordination in health. Methodology: This is an exploratory methodological study of a qualitative nature. This study seeks to explore strategic actors' perceptions of an evaluation model, and was developed in a process between June 2021 and March 2024. The following stages were followed: Identification of previous models available in the literature, model development, model validation, model update. We performed a nominal group consensus technique online with seven experts. Stages taken to define the design of the model: sending the elaborated model, together with an electronic form with 18 subjective questions, such as brainstorming strategy, for recording impressions, judgment of agreement and suggestions; workshop for discussion by videoconference, at the time the objectives and the model diagram were presented, followed by debate with clarification of doubts and suggestions for clarification of the step-by-step design. After incorporating the suggestions, the model agreed upon in the workshop was subjected to another analysis by the same experts, sent in an online Google document, in which possible inconsistencies between the proposed model and the agreed one were verified, as well as the final agreement on the recommended proposal. At the end of this stage, with synchronous and asynchronous remote procedures, consensus was reached. Results: The proposed evaluation model presents as primary categories, structure, process and result.